EUPHEMISTIC SUBTITUTION AS A CROSS-CULTURAL PRAGMATIC STRATEGY: CONTRASTIVE ANALYSIS OF ENGLISH AND UZBEK (SCIENCE TIME JOURNAL, 2026)
This article presents a contrastive linguistic analysis of euphemisms in English and Uzbek, two typologically distinct languages that reveal fascinating parallel strategies for avoiding taboo, softening harsh realities, and navigating social conventions through language. Drawing on corpus data and sociolinguistic theory, the study examines thematic domains including death, illness, bodily functions, poverty, war, and professional status where both languages employ euphemistic substitution. The analysis demonstrates that while surface forms differ markedly, the underlying cognitive motivations are largely universal, shaped by shared human experiences of shame, fear, and politeness. Cultural specificities, including Islamic influences on Uzbek euphemism and Anglo-American corporate culture on English, are also explored. The findings contribute to a broader understanding of how language mediates reality across diverse cultural contexts.